High-fat medium and circadian transcription factors (cryptochrome and clock) contribute to the regulation of cholesterogenic Cyp51 and Hmgcr genes in mouse embryonic fibroblasts - Fink, Martina (Acta chimica slovenica, 2008)
The aim of our research was to investigate how cholesterol, unsaturated fatty acids and circadian genes affect the expression of cholesterogenic genes, Cyp51 and Hmgcr, in somatic and in embryonic fibroblast cell lines. We found that in immortal Hepa1-6 cells cholesterol represses the transcription of Hmgcr and Cyp51 for 80%, while unsaturated fatty acids have different effects: Hmgcr was repressed for 50%, but Cyp51 was unaffected by the presence of linoloeic acid. In embryonic fibroblasts the abundance of cholesterol in the media did not repress the expression of Cyp51 and Hmgcr, while the presence of linoleic acid repressed transcription of both genes for 40%. Mutation of the Clock gene activated the basal transcription of Cyp51 and Hmgcr and also reconstituted the cholesterol feedback loop, that was lacking in the wild type embryonic fibroblasts. Deletion of repressor genes Cry1 and Cry2 resulted in activated transcription of cholesterogenic genes after addition of linoleic acid, while response to cholesterol was unchanged compared to wild type embryonic fibroblasts. Our results indicate that cholesterol, unsaturated fatty acids and the circadian transcription factors participate in the regulation of cholesterogenesis through different molecular mechanisms, presumably using different SREBP transcription factors and their coregulatory proteins.
Keywords: biokemija; biosinteza; holesterol; izražanje genov; molecular biology; molekularna biologija; poskusi na živalih